Services, Inequality, and the Dutch Disease - Battaile, Bill; Chisik, Richard; Onder, Harun (World Bank Group, Washington, DC, 2014)
This paper shows how Dutch disease effects may arise solely from a shift in demand following a natural resource discovery. The natural resource wealth increases the demand for non-tradable luxury services due to non-homothetic preferences. Labor that could be used to develop other non-resource tradable sectors is pulled into these service sectors. As a result, manufactures and other tradable goods are more likely to be imported, and learning and productivity improvements accrue to the foreign exporters. However, once the natural resources diminish, there is less income to purchase the services and non-resource tradable goods. Thus, the temporary gain in purchasing power translates into long-term stagnation. As opposed to conventional models where income distribution has no effect on economic outcomes, an unequal distribution of the rents from resource wealth further intensifies the Dutch disease dynamics within this framework.